2012
DOI: 10.4103/0972-2327.94989
|View full text |Cite
|
Sign up to set email alerts
|

Need for a national epilepsy control program

Abstract: This article briefly outlines the proposed national epilepsy control program. The content of the article is based on four meetings held by invitation of the Ministry of Health. Invitees by ministry – Drs. D. C. Jain, M. Gourie Devi, V. Saxena, S. Jain, P. Satish. Chandra, M. Gupta, K. Bala, V. Puri, K. S. Anand, S. Gulati, S. Johri, P. S. Chandra, M. Behari, K. Radhakrishnan, D. Bachani. Presentations were made by Dr. M. Tripathi.The program will involve all neurologists across the country in teaching and trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…According to these studies, EIs reported having lost friends and having felt isolated and rejected by the community after a seizure (19,22) . It is also noteworthy that findings obtained in other studies (23) , similarly to the ones found in this research, show that individuals with limited knowledge about epilepsy may be frightened by the physical manifestation of seizures, characteristic of epilepsy, which may contribute to the perpetuation of stigma.…”
Section: Discussionsupporting
confidence: 86%
“…According to these studies, EIs reported having lost friends and having felt isolated and rejected by the community after a seizure (19,22) . It is also noteworthy that findings obtained in other studies (23) , similarly to the ones found in this research, show that individuals with limited knowledge about epilepsy may be frightened by the physical manifestation of seizures, characteristic of epilepsy, which may contribute to the perpetuation of stigma.…”
Section: Discussionsupporting
confidence: 86%
“…The plant has different names in different languages of India such as: English: Ridged gourd, angled loofah, ribbed gourd, Chinese okra, silk squash (En); Hindi: Turai, Kadaviturai; Marathi: Dodaka; Sanskrit: Dhamargava, Koshataki; Bengali: Titotorai, Titojhinga, Titodhundal, Jhinga, Ghoshalata; Kannada: Kahire, Kahi heere, Naaga daali balli; Malayalam: Athanga; Tamil: Itukari, Itukarikkoti, Kacappi, Kacappuppirkku, Kaccam, Kaippuppirkku, Karniti; Telugu: Adavibira, Chedubira, Sendubirai, Adavi beera, Chathi beera (Nadkarni, 1996). …”
Section: Botanical Aspectsmentioning
confidence: 99%
“…The dried fruit powder is useful in preventing premature graying of hair. The root of the plant is laxative and used in dropsy (Nadkarni, 1996). …”
Section: Traditional Uses and Ethnopharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…The second is to educate locally practising doctors and get them to take on a greater role in epilepsy care with support from specialists [7]. The exact operational details of these systems of care has not been fully documented but if either group is to take over a greater role in epilepsy care they will need some tools to help them.…”
Section: Introductionmentioning
confidence: 99%